(untitled) (Circe de clásicos y modernos, 2026)
This paper offers the first Spanish translation of the Epitoma rerum gestarum Alexandri Magni (also known as “Metz Epitome”), an anonymous Latin historical account written in Late Antiquity. It covers the events of Alexander the Great’s Asian campaign between 330 and 325 BC. The text is accompanied by an introduction, as well as textual, literary, historical, and geographical notes.